(untitled) (Journal of Science and Technology, 2016)
This paper deals with safety in the Nigerian construction industry. Three aspects of safety were identified as paramount in the study and include accident causations, accident prevention and the most violated safety rules and regulations. The various factors that affect these aspects were identified and questionnaires were used to collect information related to these factors which were analyzed using the 2-step ordinal scale analytical procedure. Only factors relating to causes of accidents and the violation of safety rules are discussed due to limitation in scope. However the majority of factors identified as being responsible for the safety situation in the Nigerian construction industry were found to be human factors and their solutions will involve the prudent management of both men and material resources by the contractor.